Tungku Pemanas Logam Inovatif Untuk Proses Perlakuan Panas Berbahan Bakar Gas LPG - Andriansah, Febri; Arif, Zainal; Suheri (Fakultas Teknik Universitas Samudra, 2025)
This LPG gas-fueled metal heating furnace is designed to support heat treatment and metal smelting processes in small to medium-scale industries. With dimensions of 50 × 90 × 67 cm, this furnace is equipped with a 3600 RPM Sumura burner and blower to improve combustion efficiency and even heat distribution. The wall structure consists of SK32 firebrick, a fireproof blanket, caliboard, and an iron plate as outer protection. This layered insulation system aims to contain the heat in the combustion chamber so that it does not propagate out excessively. Tests showed that the combustion chamber temperature (T6) reached 1023°C in 60 minutes. The temperature decreases gradually from the inner to the outer layers: T5 (SK32 brick) 832°C, T4 (outer brick) 69°C, T3 (fiber blanket) 49°C, T2 (clapboard) 45°C, and T1 (iron plate) 43°C. The total heat transfer by conduction was recorded at 20.671 kW. These results show that the layered insulation design is effective in maintaining thermal efficiency and improving user safety. This furnace design has great potential to be applied in metal heat treatment activities by small industry players because it is energy efficient, easy to control, and economical. This research also opens up further development opportunities, such as the integration of an automatic control system and optimization of the shape of the combustion chamber.